Cross-Sectional Study: The Relationship Between Support Parents and Depression Levels New College Student - Rizki, Meirna Mega; Dian Eka Sari, Jayanti; Aidi, Bagas; Febrianti Rahayu, Ajeng; Imey Pratiwi, Xindy (Universitas Negeri Semarang, 2021)
Support Parents is the important thing and needed by a child especially in the transition as a new college student if they wander. This situation is causing new college students to be prone to depression. The purpose of this research is to analyze the support of parents with depression in new college students. Data collection was done using a questionnaire online with 110 respondents. The research was done in May-June 2020 on first-year students at Ailangga University Banyuwangi Campus. Data analysis using the chi-square. The result showed that the dimensions of parental support in the form of instrumental support (Ï=0.036) and appreciation support (Ï=0,00) having relationships because Ï values < 0,05. The research indicated that the majority of new students suffer from depression in the high category (50,9%). The result of the chi-square relationship supports parents with depression level in first college students = 0,012 (Ï<0,05). The value of Ï obtained less than 0,05 means there is a significant relationship between support parents with the level of depression in new college students. The result of this research can be used as reference policies on activities that will be held by the campus for the new college students, with the aim of preventing or reduce depression in new college students. This research can also be a reference for parents in providing support to their children.